Determinants of Household Latrine Ownership in The River Basin Communities - Putri Maharetha; Yustini Ardillah; Dwi Septiawati; Rafika Oktivaningrum (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Lack of household sanitation is a pressing problem in the household sanitation of many rural communities in Indonesia, and Ibul besar village is not an exception. Although the government has implemented different programs to encourage people to improve their sanitation, the latrine ownership among the residents is low. An objective of this study was to identify the important factors that determined the ownership of latrines at the household level in Ibul Besar Village, Pemulutan District, and Ogan Ilir Regency. It was a quantitative cross-sectional study conducted on 124 respondents who were selected using purposive means through structured interviews and questionnaires. Chi-square was used to analyze data. The results showed that clean water source, household income, and housing density were significantly associated with latrine ownership. Conversely, education level, access to health information, knowledge, and attitude were not significantly related. Enhancing access to clean water and assisting the low-income households with the help of financial or land-use policy measures are crucial measures to augment the household ownership of latrines in rural societies.